One of the 5-aminosalicylates drug, mesalamine as a drug repurposing lead against breast cancer - Swami, Dayanand (2023)
The docking analysis of aminosalicylates (mesalamine sulfasalazine olsalazine balsalazide) was done using AutoDock Vina software. The program generated 10 possible docking conformations of the ligand for each of the selected receptors. From the possible conformation, the best conformation was selected based on the binding energy and stability (number of hydrogen bonds, pi–pi, or van der Waals interactions). The grid box parameter used for docking was set as following Topoisomerase II: x = 48, y = 34, z = 36, center: x = 30.391, y = − 2.116 and z = 38.776; Aromatase: x = 44, y = 40, z = 42, center: x = 86.146, y = 47.820 and z = 41.261. There are amino acids reported in the Topoisomerase II and Aromatase proteins that anchor the ligand in the binding site. In Topoisomerase II, GLU 87, ASN 91, ASN 120, SER 148 and LYS 168 are actively involved in the site. Whereas in Aromatase, ILE 305, ALA 306, ASP 309 (I helix), PHE 221 and TRP 224 (F helix), and ILE133 and PHE 134 from the BC loop also play a major role in the binding site. Moreover, VAL 370, LEU 372 and VAL 373 from the K helix β3 loop and LEU 477 and SER 478 in the β8–β9 loop also significantly affect the stability